(untitled) (Al-Qamar, 2025)
This article explores the unique and reformist approach of Allama Tamanna Imadi towards Quranic interpretation. He is characterized by his inclination to diverge from traditional narratives and his commitment to interpreting the Qur’an primarily through the Qur’an itself. This methodology often led him to conclusions that were not only different from but at times in direct opposition to the consensus of mainstream Sunni exegetes. In certain instances, he openly rejected the views of classical scholars and insisted on his interpretations as definitive. For example, he held the controversial belief that during the first revelation in the Cave of Hira, a written form of the Qur’an was presented, taught to the Prophet ﷺ, and even transcribed by him contrary to the established Sunni narrative of the Prophet’s illiteracy at that time. Furthermore, he strongly opposed the practice of enslaving war captives and equated sexual relations with female slaves without marriage to fornication. He also asserted that the Qur’an was compiled and codified during the Prophet’s lifetime, dismissing the traditional view that this occurred during the caliphate of Abu Bakr (RA), considering the latter claim to be a fabrication introduced by later figures.